Nitrogen-rich biomass derived three-dimensional porous structure captures FeNi metal nanospheres: An effective electrocatalyst for oxygen evolution reaction. (22nd March 2022) - Hou, Guoyu; Wu, Jiang; Li, Tong; Lin, Jia; Wang, Baofeng; Peng, Lin; Yan, Ting; Hao, Lingsheng; Qiao, Lingxia; Wu, Xuefei
Abstract: Electrochemical water splitting is a sustainable hydrogen energy transfer, storage, and transportation technology, but it is limited by the oxygen evolution reaction (OER) in practical applications. Here, three-dimensional porous nanostructures anchored by metal nanospheres were successfully prepared based on low-cost biomass as a carbon-based material, which was modified with FeNi bimetallic nanospheres and treated through temperature-programmed annealing and nitridation of FeNi(x) precursors. Moreover, in this article, the influence of morphology and valence changes caused by different metal ratios on the performance of OER is explored. Specifically, FeNi(2) /NC-800 showed a lower over-potential as low as 250 mV at a current density of 10 mA cm −2 and a slight Tafel slope of 70 mV dec −1 OER in 1 M KOH, which is better than that of the noble metal catalyst. The electrochemical impedance spectrum (EIS) test shows the most negligible diffusion resistance. Moreover, the anchoring of metal nanospheres on the nitrogen carbon substrate can provide more stable morphology characteristics for the catalyst, which shows excellent durability at 1.48 V. The excellent OER performance is attributed to the excellent electron transport efficiency provided by the unique morphology and the synergistic effect between FeNi-N-C. Highlights: Biomass derived three-dimensional porous structure to maximize the role of active sites. FeNi Alloy nanospheres are trapped on porous carbon substrates. Nitrogen-rich doped FeNi metal sphere catalysts exhibit high oxygen release activity.